Algerian Pharmaceutical Industry: Prospective Structural Analysis Using MICMAC Method - Houssame Eddine, BALOULI (Dirassat Journal Economic Issue, 2022)
This work aims to determine the key variables that control the development of the Algerian pharmaceutical industry in the long term using structural analysis by MICMAC method. After listing the variables, filling in the matrix of direct influences, and analyzing the indirect potential plan we select the key variables, which are Research and Development, Consumption, innovation, the level of production, production costs, and marketing/sales. We can add other regulatory variables such as human capital, partnership with foreign countries, research costs, prices, and investment.